Scattering Analysis and Detection of Layered Plate Debonding Using Guided SH Waves with Boundary Element Method - Supawat Wongthongsiri; Sohichi Hirose (Shock and Vibration)
This paper investigates the scattering behavior of guided shear horizontal (SH) waves in a two-dimensional, isotropic, and linear elastic layered plate with partially debonded interface by analyzing the reflection and transmission coefficients of scattered waves. The partial wave technique is established to form the displacement and stress of guided wave functions, and the boundary element method (BEM) is utilized to handle the numerical calculation with elastodynamic fundamental solutions in the frequency domain. After applying proper boundary conditions including continuity condition on the interface with traction-free debonding, the scattering coefficients can be obtained in terms of boundary element solutions. Two different materials (steel and aluminum) with various debonding lengths and locations in a 1 mm double-layered plate are considered. With several modes of the incident wave over a frequency range up to 4.5 MHz, the variations of scattering coefficients and scattering phenomena are numerically investigated as several parameters such as mode of the incident wave, materials, locations, and length of debonding are changed. The numerical results also suggest the potential of the suitable wave mode for the debonding detection, which can be useful for non-destructive inspection.